Menata Ulang Masa Depan: Bagaimana Digitalisasi Logistik Dapat Mengkatalisasi Kinerja Ekonomi Pasca Pandemi Covid-19 - Muhammad Firdaus Al Farohi; Muhammad Zaky Nur Fajar; Mukti Ali (EKONOMI DAN BISNIS DIGITAL, 2023)
The COVID-19 pandemic has caused significant changes in various aspects of life, especially in the economy sector in Indonesia in general and East Java Province specifically. The poor performance of Indonesia's logistics has been further burdened by the pandemic, hindering the industry as the main driver of the nation's economy. However, the pandemic that forced the entire community to adapt to the new normal era sparked the growth of digitalization. This is a breath of fresh air for the logistics aspect to utilize digital technology to achieve efficiency and re-drive economic growth. Using the digital competitiveness data (EV-DCI) and other digitalization indicators obtained from the Central Statistics Agency, this study attempts to prove the impact of digitalization at the provincial level in Indonesia on per capita GRDP growth through a reduction in logistics costs. This logistics cost reduction is assumed to be reflected in the Consumer Price Index for the transportation sector. From the 2SLS method used, although not statistically significant, the decrease in transportation CPI due to digitalization described by the increasing number of internet users, smartphone owners, and BTS in each province in Indonesia has an indicative impact to encourage economic performance. Through qualitative analysis, this study suggests policymakers, especially in East Java Province, to encourage digitalization in the logistics sector through the use of Warehouse Management System (WMS), Blockchain, and Transportation Management System (TMS) technologies in industries in East Java to optimize operational and cost efficiency